PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN GOOD GOVERNMENT GOVERNANCE SEBAGAI VARIABEL INTERVENING - Hasanah Tisna Amijaya (STMIK Mardira Indonesia, Bandung, 2019)
Accountability of a financial report is one of the foundations for the creation of good governance, prioritizing the use or management of finance that requires public funds. By fulfilling the basics of financial reporting which is a principle of good governance, the government as the manager of regional finance will automatically increase accountability and trust from the community.With the application of good internal control, it is expected to be able to create financial reports that are accountable, resolved with good governance. This study used descriptive analytical research method. Based on statistical analysis of the obtained coefficient of determination 64,1%. with a significance level of 5%. The results showed that the internal control variables gave rise to positive accountability towards the local government financial statements,with good governance as an intervention. Keyword : Internal Control System, Good Government Governance, Accountability of a financial statement local governmentDOI : http://doi.org/10.5281/zenodo.3631047